(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The european civil procedure law from the beginning of the XXI century onwards as never before is the focus of scientific interest. Wind in the back of this trend is the professor’s law of European universities which is slowly, but surely differentiating the european civil procedure law from international civil procedural law and distinguishing it in an independent scientific discipline. It is precisely because of this, this paper analyze the possibility of scientific development of the european civil procedure law through the prism of the ideals of the great European legal schools, the stages of development of the european civil procedure law that differentiate the european civil procedure law from international civil procedural law, as well as the term, the basic subject and objectives around which the the european civil procedure law should be built as a scientific discipline.